2015
DOI: 10.1186/s13023-015-0313-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after allogeneic hematopoietic stem cell transplantation for metachromatic leukodystrophy: the largest single-institution cohort report

Abstract: BackgroundMetachromatic Leukodystrophy (MLD) is a rare, fatal demyelinating disorder with limited treatment options. Published outcomes after hematopoietic stem cell transplantation (HSCT) are scant and mixed. We report survival and function following HSCT for a large, single-center MLD cohort.MethodsTransplant-related data, survival and serial measures (brain MRI, nerve conduction velocity (NCV), neurologic and neuropsychology evaluations) were reviewed. When possible, parental interviews informed current neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
162
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 43 publications
2
162
0
2
Order By: Relevance
“…New therapeutic approaches are currently under investigation 1, 15. There is an increasing body of evidence suggesting that successful therapy is related to early treatment, that is, presymptomatic and early symptomatic,16, 17, 18, 19 and to a slower disease progression, that is, treatments such as HSCT being more effective in the more slowly progressive juvenile form than in the rapidly progressive late‐infantile form 17, 18. Thus, one of the clinical challenges when to recommend HSCT in juvenile MLD is to judge on the dynamics of the disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New therapeutic approaches are currently under investigation 1, 15. There is an increasing body of evidence suggesting that successful therapy is related to early treatment, that is, presymptomatic and early symptomatic,16, 17, 18, 19 and to a slower disease progression, that is, treatments such as HSCT being more effective in the more slowly progressive juvenile form than in the rapidly progressive late‐infantile form 17, 18. Thus, one of the clinical challenges when to recommend HSCT in juvenile MLD is to judge on the dynamics of the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems important to investigate whether the demyelination load is a clinically relevant parameter, not only to describe, but also to predict disease progression in juvenile MLD. Especially, as HSCT was proven to be a beneficial treatment when done at an early stage of the disease before the phase of rapid progression 16, 17, 18, 19. It seems essential to find predictors of disease progression already early during disease course in order to be able to judge on the “window of opportunity,” for example, whether a treatment has enough time to become effective.…”
Section: Introductionmentioning
confidence: 99%
“…However, his diagnosis allowed the detection of patient MLD8b before disease onset. And indeed, two recent studies -a prospective cohort and case-control study -have raised evidence that HSCT is associated with a reasonable chance of disease stabilization if performed pre-symptomatically 10,16 . Patient MLD-9 came for HSCT evaluation one year after the beginning of cognitive losses.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports suggested that HSCT might reduce demyelination in juvenile (onset between two and 14 years) and adult forms of MLD when performed as early as possible 3,4,5,16 . A recent case control study confirmed that HSCT, at a presymptomatic or early symptomatic stage of juvenile MLD, is associated with disease stabilization 10 .…”
mentioning
confidence: 99%
“…In an individual analyses, for MLD (OMIM #250100), the HSCT performed before symptoms onset could delay the progression of central nervous system compromise, but the response at the peripheral level is still controversial in the litterature 4,5 . For MPS-IH (OMIM #607014), although cerebral damage prior to HSCT remains irreversible, HSCT treatment could still offer an improvement of neurological development, particularly when HSCT is done performed 16 months of age, when a significant reduction of brain atrophy is observed (OR 3.22, 95%CI 1.60-6.50, p = 0.001) 6 .…”
mentioning
confidence: 99%